The Polish-Ukrainian borderland through the prism of convergence and resilience from 2004 to 2020 - Łaźniewska, Ewa; Górecki, Tomasz; Siemiatowski, Fabian (Bulletin of Geography. Socio-economic Series, 2026)
The escalation of the conflict in Ukraine in February 2022 highlighted the need for a fresh approach to regional economic analysis. This study examines the relationship between convergence and resilience in border regions, focusing on the period from 2004 to 2020. Resilience was measured by GDP per capita, while convergence was assessed using the σ-convergence test. Data were sourced from Statistics Poland and the State Service of Statistics of Ukraine. The results show that, although the 2008 crisis impacted Ukrainian regions, border regions in both Ukraine and Poland demonstrated a greater capacity to recover. Ukrainian border regions, in particular, exhibited faster recovery compared to non-border regions (nBR). The research also indicates that regions with greater convergence are more resilient. This finding is crucial to understanding the ongoing economic impact of the war in Ukraine, highlighting the critical role of border regions in the economies of both countries.